2019
DOI: 10.1016/j.automatica.2018.10.037
|View full text |Cite
|
Sign up to set email alerts
|

Linear SLAM: Linearising the SLAM problems using submap joining

Abstract: The main contribution of this paper is a new submap joining based approach for solving large-scale Simultaneous Localization and Mapping (SLAM) problems. Each local submap is independently built using the local information through solving a small-scale SLAM; the joining of submaps mainly involves solving linear least squares and performing nonlinear coordinate transformations. Through approximating the local submap information as the state estimate and its corresponding information matrix, judiciously selectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…The second mode addresses area coverage with uncertainty using an SQP method. In order to improve computational efficiency in both of these modes, Linear SLAM [16] is applied. Finally, simulations and experiments with an aerial robot are presented to verify the running-time efficiency of this framework.…”
Section: Introductionmentioning
confidence: 99%
“…The second mode addresses area coverage with uncertainty using an SQP method. In order to improve computational efficiency in both of these modes, Linear SLAM [16] is applied. Finally, simulations and experiments with an aerial robot are presented to verify the running-time efficiency of this framework.…”
Section: Introductionmentioning
confidence: 99%
“…The basic idea is to divide the full PGO into several submaps (i.e., subgraphs), solve each one of them, and then join the submaps together to obtain an approximation to the full PGO. Zhao et al [35], [36] investigated the special case of joining two submaps, with a clever parameterization, which can be solved by a linear least squares, followed by a nonlinear transformation. For 2-D cases, Carlone et al [37] suggested a linear approximation framework to PGO, by computing first an orientation estimation, and then the position part using the given orientation.…”
Section: Related Workmentioning
confidence: 99%
“…For 3D feature-based SLAM, a simulated dataset is used with a trajectory of 870 poses and uniformly distributed features in the environment as used in [26]. Both Full-NLLS in (9) and the proposed Pose-Only algorithm (for 3D scenario) are performed.…”
Section: B 3d Feature-based Slammentioning
confidence: 99%